Executive functions in health and disease - Goldberg, Elkhonon (Academic Press, 2017)
"Executive Functions in Health and Disease provides a comprehensive review of both healthy and disordered executive function. It discusses what executive functions are, what parts of the brain are involved, what happens when they go awry in cases of dementia, ADHD, psychiatric disorders, traumatic injury, developmental disorders, cutting edge methods for studying executive functions and therapies for treating executive function disorders. It will appeal to neuropsychologists, clinical psychologists, neuroscientists and researchers in cognitive psychology."--Provided by publisher.